MANAJEMEN PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN PKBM (Studi Tentang Efektivitas Pengelolaan PKBM Bonti Sukses Abadi, PKBM Setia Mandiri dan PKBM Peduli Anak Bangsa di Kota Bandung) - Abduloh Sidik Mustopa (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2022)
Education is a learning experience that has programs in formal, non-formal or informal education in schools that last a lifetime which aims to optimize the consideration of individual abilities, so that in the future they can play their roles appropriately. Non-Formal Education is a solution for children and adults who drop out of school, besides that, with Non-Formal Education, Education Services can serve anyone, because obtaining education, knowledge and knowledge can be done in a formal or non-formal way. the education management process includes planning, organizing, implementing, monitoring and evaluating. Through good planning, PKBM is expected to become a truly effective forum for community empowerment, so as to be able to improve the quality of life of the community as expected and ultimately be able to improve the quality of human resources as a whole. The general objective of this research is to determine the effectiveness of PKBM management. Medium The specific purpose of this study is to determine the effectiveness of planning, organizing, implementing, controlling and evaluating PKBM. This research method is evaluative, collecting data through interviews, observation, and documentation. The results of this study indicate that the effectiveness of the management at PKBM Bonti Sukses Abadi, PKBM Setia Mandiri and PKBM Peduli Anak Bangsa has been effective, both from the analysis of planning, organizing, implementing, controlling and evaluating, because of management. In accordance with the standards of PKBM management and based on the analytical standards of PKBM Bonti Sukses Abadi, PKBM Setia Mandiri and PKBM Peduli Anak Bangsa scored 100%. This means that all affective aspects. The management carried out in PKBM is running according to the initial planning. This is said to be very effective because based on the results of observations and interviews about the implementation of PKBM management, some of the questions resulted in referring to existing indicators, namely implementing the learning process, carrying out the learning assessment process, and Sriwijaya PKBM also carrying out a final evaluation. However, there is one obstacle that often occurs in learning residents who are often absent during learning. but this has been followed up by the head of PKBM by reminding them of the importance of science.